Uranium radionuclides and organic biomarkers in sediment core RC27-42 - Pourmand, Ali; Marcantonio, Franco; Bianchi, Thomas S; Canuel, Elizabeth A; Waterson, Elizabeth J (Supplement to: Pourmand, A et al. (2007): A 28-ka history of sea surface temperature, primary productivity and planktonic community variability in the western Arabian Sea. Paleoceanography, 22(4), PA4208, https://doi.org/10.1029/2007PA001502, 2014)
Uranium series radionuclides and organic biomarkers, which represent major groups of planktonic organisms, were measured in western Arabian Sea sediments that span the past 28 ka. Variability in the past strength of the southwest and northeast monsoons and its influence on primary productivity, sea surface temperature (SST), and planktonic community structure were investigated. The average alkenone-derived SST for the last glacial period was ~3°C lower than that measured for the Holocene. Prior to the deglacial, the lowest SSTs coincide with the highest measured fluxes of organic biomarkers, which represent primarily a planktonic suite of diatoms, coccolithophorids, dinoflagellates, and zooplankton. We propose that intensification of winter northeast monsoon winds during the last glacial period resulted in deep convective mixing, cold SSTs and enhanced primary productivity. In contrast, postdeglacial (<17 ka) SSTs are warmer during times in which biomarker fluxes are high. Associated with this transition is a planktonic community structure change, in which the ratio of the average cumulative flux of diatom biomarkers to the cumulative flux of coccolithophorid biomarkers is twice as high during the deglacial and Holocene than the average ratio during the last glacial period. We suggest that this temporal transition represents a shift from a winter northeast monsoon-dominated (pre-17 ka) to a summer southwest monsoon-dominated (post-17 ka) wind system.